UPAYA PENINGKATAN OMSET USAHA TENUN TAJUNG MELALUI KREDIT PERBANKAN - Pridson Mandiangan (JURNAL RISET TERAPAN AKUNTANSI, 2018)
One of the functions of banking is as agents of development. This function requires the bank to provide banking services with a purpose the creation of the stability of the country's development and the welfare of society. One of the ways that can be reached is by granting programs credit to the customer's sector of small and medium enterprises. This study aims to analyze the influence of Credit Banking on the Turnover of Tenun Tajung Business in Tuan Kentang Palembang . What are the obstacles that occur and how to overcome these obstacles. The study used primary data from 30 respondents in the area of Tuan Kentang Palembang. The technique used is simple random sampling. The method used is linear regression to know the effect of Credit Banking to Turnover Tenun Tajung Business. The results showed that the independent variables, that are Credit Banking both partially and simultaneously affect the dependent variable, the turnover of Tenun Tajung Business.